SUITABLE PACKAGING CONCEPT FOR SUNGKAI LEAVE HERBAL TEA PRODUCED BY THE INDEPENDENT AGRICULTURAL AND RURAL TRAINING CENTRE “SUNGKAI PERMAI” - Syukri, Daimon; Rini, Rini; Makky, Muhammad (Andalasian International Journal of Social and Entrepreneurial Development, 2022)
Background: Sungkai leave herbal tea produced by The Independent Agricultural and Rural Training Centre “Sungkai Permai” need to be expanded by packaging improvement. Methodology: The concept of packaging for herbal tea has been developed by the team from Andalas University. The basic design and brand for the herbal tea has proposed and produced in order to enhance the satisfaction of consumers to existing tea. Conclusion: The Independent Agricultural and Rural Training Centre “Sungkai Permai) was impressed for the packaging concept of their Sungkai leave herbal tea. “Teh Sehat Sungkai” is the brand that was created for the herbal tea product. Moreover, the utilization of ivory box include with the design was also introduce to the The Independent Agricultural and Rural Training Centre “Sungkai Permai). Further development is needed for increasing the acceptance of consumers to the Sungkai leave herbal tea product.